EDUKASI PENGGUNAAN TANAMAN OBAT KELUARGA SEBAGAI UPAYA PENCEGAHAN STUNTING DESA MULYOREJO - Alvia, Yundha; Rochmayanti, Dewi; Lita Agustina, Nur; Wahid Mukarom A, Abdul; Irawan, M. Alif Dhuhri; Baqiyatus Sholihah, Umi; Wijayani, Susi Mei (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Stunting is a serious health problem in Indonesia that can affect children's physical growth and cognitive development. This service aims to explore the use of family medicinal plants (TOGA) as an effort to prevent stunting in children. Family medicinal plants have great potential in providing important nutrients and bioactive compounds that can support optimal growth. The service methods used are literature studies and surveys of the community regarding knowledge and practice of using TOGA. This educational outreach was carried out on October 27 2024 by STIE Scholar Bojonegoro students. Community service activities focus on premarital mothers and teenagers in Mulyorejo Village, Singgahan District, Tuban Regency. This community service activity ran smoothly and the community was actively involved in outreach. The implementation of education about toga plants as an effort to prevent stunting in Mulyorejo Village has shown positive results. This program can be recommended as an intervention model to improve the nutritional status of the community, especially for children under five and pregnant women in order to prevent stunting more broadly.